Hand Puppet Berbasis Tema: Media Bercerita untuk Anak Usia Dini - Jazariyah, Jazariyah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2018)
The purpose of this study is to produce appropriate and effective theme-based hand puppetmedia to be used as a medium for storytelling in early childhood. This research model uses adevelopment model (R & D) by adopting the following stages: potential problems, informationcollection, product design, design validation, design revisions, products, small-scale producttrials, large-scale trials and mass production. In this study not all stages are carried outconsidering the limited time and cost so that the research only reaches the stage of feasibilityvalidation and design revision to be the final product. The feasibility of this theme-based handpuppet is based on expert testing and assessment from users. Based on data analysis, the resultsof this study indicate that theme-based hand puppets are sufficient to be used as media. Forthat according to user ratings, more than 50%